An Empirical Analysis of Liquidity and its Determinants in The German Intraday Market for Electricity - Simon Hagemann; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
This paper presents a theoretical and empirical analysis of liquidity in the German intraday market for electricity. Two models that aim at explaining intraday liquidity are developed. The first model considers the fundamental merit-order and intraday adjustment needs as the drivers of liquidity in a perfectly competitive market. The second model relaxes the assumption of perfect competition in the intraday market and assumes that the trading behavior of profit maximizing market participants influences the liquidity provision. The relevance of commonly used liquidity indicators like the bid ask-spread, resiliency, market depth, price variance, delay and search costs as well as trading volume and the number of trades are analyzed with respect to both models of liquidity. The empirical findings indicate that liquidity in the German intraday market can be explained by the trading model while the purely fundamental model is rejected.
Keywords: L94; Q41; 330; Intraday market; electricity; liquidity; fundamental model; trading model